Acercamiento a la rehabilitación cognitiva en personas con discapacidad intelectual a partir del uso de programas computarizados: una revisión al concepto de discapacidad intelectual. - Acosta Echavarría, Álvaro Alejandro; Díaz Soto, Cecilia María (Revista Pensamiento Americano)
Introduction: This article analyzes the evolution of the concept of intellectual disability (ID), its epidemiology, etiology, and cognitive interventions supported by computerized programs. Objective: To examine the most relevant studies on computerized cognitive rehabilitation in people with ID, highlighting findings, limitations, and future projections. Methodology: A reflective review and critical analysis of scientific literature published between 2010 and 2024 was conducted. Databases such as Scopus, PubMed, SciELO, Dialnet, and Google Scholar were consulted, applying inclusion criteria (articles in English/Spanish, empirical studies, systematic reviews, and quasi-experimental studies) and exclusion criteria (gray literature, duplicates, lack of full access). Twenty-eight articles were selected: 11 on ID, 11 on computer programs, and 6 on the etiology of ID. Results: The literature shows that computer programs favor working memory, executive functions, and adaptive behavior, although limitations persist in the duration of interventions and methodological heterogeneity. Conclusions: It is confirmed that the appropriate term is intellectual disability. Technological interventions have positive effects on learning and quality of life, but more longitudinal and experimental studies are needed to define optimal programs in terms of duration, age, and mode of application.